The Boyâ€™s Morality as Reflected in Laura E. Richardsâ€™ The Golden Windows - Putra, Refinsa Raditya; Hadiyanto, Hadiyanto (Proceedings International Conference of Culture and Sustainable Development; Vol 3 (2025): PROCEEDINGS ICOCAS, 2025)
This research paper discusses the portrayal of morality of the boy in The Golden Windows written by Laura E. Richards. The objective of this research paper is to analyze the portrayal of the boy, the main character of the short story, the factors that influence the boyâ€™s morality, and the effects of the boyâ€™s morality growth. Using a library research method, the writer collects both primary data from Richardsâ€™ original short story and secondary data from scholarly sources on moral development and literary analysis. The writer analyzes the data by employing moral approach that foregrounds ethical reasoning in literature by using Lawrence Kohlbergâ€™s theory of morality. The results of this research reveal that the boy is characterized through both direct and indirect means as hardworking, curious, generous, innocent, responsible, and ultimately emotionally mature, demonstrating a blend of innate virtues and learned behaviors. His journey through obedience, self-interested exploration, and positive social relationships shows how his rural upbringing, freedom to think independently, and emotional guidance of family and community shape his moral outlook. His transformative development fosters decisive decisionâ€making and solidarity, underscoring literatureâ€™s role in promoting ethical consciousness.
Keywords: Portrayal of Morality, Factors of Morality, Effects of Morality